Fazail -e- amal - Kandhalvi, Muhammad Zakkriyya (Ferozesons; Pakistan, 2002)
Fazail-e-Amal is a collection of teachings and virtues from Islamic traditions, emphasizing the importance of good deeds and righteous actions in daily life.